Greek μάρις — a Forgotten Name for Long Pepper - Rosół, Rafał (Collectanea Philologica, 2025)
The Greek word μάρις ‘long pepper (Piper longum L.)’ that is attested in the lexicon of Hesychius (μ 289) has not been the subject of any research to date. The author’s hypothesis is that it is ultimately of Indo-Aryan origin (cf. Sanskrit marī̆ca- m. ‘pepper shrub’, marī̆ca- n. ‘black pepper’, Pali marica- n. ‘id.’, Prakrit maria-, miria- m./n. ‘id.’, etc.). However, it is difficult to say whether the Greeks borrowed μάρις directly from a language spoken in India or via another Oriental language (perhaps Iranian; cf. Modern Persian marič (mareč, murč) ‘pepper’).